Multiwinner candidacy games - Obraztsova, S; Polukarov, M; Elkind, E; Grzesiuk, M (International Foundation for Autonomous Agents and Multiagent Systems, 2020)
In strategic candidacy games, both voters and candidates have preferences over the set of possible election outcomes, and candidates may strategically withdraw from the election in order to manipulate the result in their favor. In this work, we extend the candidacy game model to the setting of multiwinner elections, where the goal is to select a fixed-size committee of candidates, rather than a single winner. We examine the existence and properties of Nash equilibria in the resulting class of games, under various voting rules and voter preference structures.